Smart sensor to detect ripeness of fruits - Nur Fadhilah Abdul Hamid (2017)
Global food wastage is a major factor for sustainable development for both developed and developing countries. Food wastage arises when global food supplies are being lost and wasted through the supply chains and this may eventually lead to global food insecurity. Coupled with decreasing amount of arable land available for farming, future generations may face the brutal implications due to scarcity and shortage of nourishment. For this reason, it is vital to implement ways to reduce the amount of food wastage globally. Steps can be taken by both individuals and industries to eradicate the situation, but impacts will be multifold if done by the latter. Fruits are one of which that has the highest wastage rates of any food. At the retail level, the reason behind is due to cosmetic filtering where less-appealing food are discarded even when it is still edible. Improvements between supply chains and farmers in the transportation and food packaging will be able to reduce the amount of food loss and waste. Therefore, this study aims to cover the methods taken by industries to reduce food wastage while considering a portable chemo-resistive sensor to detect the ripeness of fruits to prevent food wastages from the over-ripening of fruits.